GENRE-BASED COURSE BOOK FOR HOSPITALITY DEPARTMENTN IN SURAKARTA - Yeni Suprihatin (Jurnal Pedagogy, 2016)
This research is aimed at designing ESP Course book at SMK Sahid Surakarta that mainly focus: To investigate the quality of existing learning book used in English teaching and learning at SMK especially in hospitality department and to describe the design of Genre-based ESP course book for hospitality department of SMK.This research and development was carried out in SMK Sahid Surakarta in the academic year of 2015/2016. The number of population was three classes (that consisted of the eighth grade of APH1,APH2, APH3. The samples were 30 students of APH1.The product of this study is the genre-based course book for hospitality department with integrated skills, syllabus and course grid as the models for lesson plan. The course book consists of standard competence, topics, basic competence (core material), general aims or indicators, teaching and learning activities, methods and media, assessment, the allotted time and sources of the materials. The role and design of instructional materials are a key to help teacher and students being bale to use language in specific context. The proposed course book consists of 2 units and each unit has a topic which is developed to 19 activities. The teaching activities included in the course book are starting point, modeling, joint construction, and independent construction. Such features are added as vocabulary notes, grammar point, useful expression, and for your information to support the fourth stages of activities.